First confirmed record of the white shark Carcharodon carcharias (Lamniformes: Lamnidae) from Indonesia. (20th May 2014) - Fahmi,; Dharmadi,
Abstract : A six metre adult male of the white shark Carcharodon carcharias was caught by demersal longliners operating off Dompu, Indonesia. The specimen was landed and sold at Tanjung Luar landing site in eastern Lombok. Photographic evidence for this specimen is provided and an upper lateral tooth was retained. This is the first confirmed record of the species in Indonesian waters.